Electronic stopping power correction for different phase shift conditions - Abeer Ali Mohamad Hussien; Dalya Abd Ali Mohammed (مجلة بغداد للعلوم, 2010)
Bloch correction is considered one of the important corrections for stopping power for its ability to connect the classic description of the (Bohr) scientist with the quantum treatment of (Bethe) scientist.